Does the promotion and application of new energy vehicles contribute to the reduction of carbon intensity? A quasi-natural experiment analysis - Shuai Wang; Jing Wang; Jiarong Cheng (Sustainable Futures)
This study examines the impact of the promotion and application of new energy vehicles (PANEVs) policy on carbon intensity across 282 Chinese cities. Using this quasi-natural experiment, the results show that PANEVs significantly reduce carbon intensity in the treated cities. Mediation analysis reveals that while the policy may lead to higher carbon intensity due to transportation industry structural upgrading and reduce carbon intensity by promoting green technology innovation. This study also finds that the heterogeneous characteristics of urban economic development, population density, and technological foundation influence the impact of PANEVs on carbon intensity. Additionally, the spatial spillover effects of PANEVs further lower carbon intensity in neighboring cities, promoting regional green integration. The results of this study provide valuable insights for policymakers involved in new energy vehicle-related initiatives.